NUANSA POLITISASI DALAM PELAKSANAAN TUGAS GURU SEBAGAI DAMPAK DARI DESENTRALISASI PENDIDIKAN - Afriantoni Afriantoni (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Education Decentralization is a fact that cannot be denied in the national system of education. Therefore, educational settings are vulnerable towards political policy played by the government that makes the government have a very dominant authority in determining the direction of education including teacher’s duty. As educators, the teachers should have professional competence, pedagogic, personality, social that can make them professional teachers. Therefore, politicizing tendency is not expected to interfere with the professional duties of teachers. As a consequency, the strategies that lead to improve the quality and welfare of teachers are necessarily needed.